Rail surface treatment – Grinding and milling – Competing or complementary technologies - Steyn, Erika (My University, 2019)
Railway maintenance programs worldwide use rail grinding to combat surface defects such as corrugations and rolling contact fatigue. However, emerging technologies including variations on rail grinding and rail milling are gaining interest in the railway maintenance industry. Limited academic literature is available on these alternative surface treatment methods. This thesis work investigates supporting literature on rail grinding and milling technologies, and provides insight into the working principles, impact on the rail surface and the application possibilities for each technology. Recommendations are made on the most suitable technology for various maintenance activities and current best practices are discussed. It has been found that conventional rail grinding dominates current practices, but technologies such as rail milling and high speed grinding are becoming increasingly popular on high density networks as in China and Germany. These methods are shown to have unique characteristics that can be used to improve railway maintenance strategies by complementing current practices.
Keywords: Rail grinding, rail milling, railway maintenance, surface treatment, surface defects, rail maintenance strategies, thermomechanical effects